Clinical Spectrum of Capillary Malformation–Arteriovenous Malformation Syndrome Presenting to a Pediatric Dermatology Practice: A Retrospective Study. Issue 1 (21st July 2014) - Weitz, Nicole A.; Lauren, Christine T.; Behr, Gerald G.; Wu, June K.; Kandel, Jessica J.; Meyers, Philip M.; Sultan, Sally; Anyane‐Yeboa, Kwame; Morel, Kimberly D.; Garzon, Maria C.
Abstract Capillary malformation–arteriovenous malformation syndrome (CM‐AVM) is an autosomal dominant disorder caused by RASA1 mutations. The prevalence and phenotypic spectrum are unknown. Evaluation of patients with multiple CMs is challenging because associated AVMs can be life threatening. The objective of this study was to describe the clinical characteristics of children presenting with features of CM‐AVM to an academic pediatric dermatology practice. After institutional review board approval was received, a retrospective chart review was performed of patients presenting between 2009 and 2012 with features of CM‐AVM. We report nine cases. Presenting symptoms ranged from extensive vascular stains and cardiac failure to CMs noted incidentally during routine skin examination. All demonstrated multiple CMs, two had Parkes Weber syndrome, and two had multiple infantile hemangiomas. Seven patients had family histories of multiple CMs; three had family histories of large, atypical CMs. Six had personal or family histories of AVMs. Genetic evaluation was recommended for all and was pursued by six families; four RASA1 mutations were identified, including one de novo. Consultations with neurology, cardiology, and orthopedics were recommended. Most patients (89%) have not required treatment to date. CM‐AVM is an underrecognized condition with a wide clinical spectrum that often presents in childhood. Further evaluation may be indicated in patients with multiple CMs. This study is limited by its small and retrospective nature.